Design of a class G audio amplifier - Zhang, Huiyuan (2011)
The demand for audio power amplifier in portable multimedia devices has been on a rise. For both manufacturers and consumers, power efficiency to maintain long battery lifetime, miniaturization to achieve smaller form factor and low Total Harmonic Distortion (THD) for quality sound synthesis are the key factors in choosing new audio gear. Linear amplifiers, such as Class A, Class B and Class AB amplifiers have low power efficiency. On the other hand, Class D amplifier which is switching amplifier, despite its relatively higher power efficiency, suffers from large form factor due to the external inductor.